Desain dan Implementasi Alat Peraga KOPSINU dalam Pembelajaran Make a Match: Dampaknya Terhadap Literasi Numerasi - Nurjanah, Siti; Basir, Mochamad Abdul (Griya Journal of Mathematics Education and Application, 2025)
This study aims to analyze the effectiveness of the KOPSINU teaching aid in the Make a Match learning model for improving students' numeracy literacy. The research is based on the low numeracy literacy of Indonesian students, which is caused by less interactive learning methods and minimal use of teaching aids. A quantitative approach with a quasi-experimental posttest-only control group design was used. The subjects consisted of 60 seventh-grade students at SMP Islam Sultan Agung 4 Semarang, divided into experimental and control groups. The research instrument was a numeracy literacy test covering aspects of mathematization, symbolization, reasoning, and argumentation. The t-test results showed a significant difference between the two groups, with the experimental group scoring higher on the posttest. These findings indicate that the use of KOPSINU significantly enhances students' numeracy literacy by creating a more interactive, engaging, and motivating learning environment that helps students actively understand mathematical concepts.